The effectiveness of case method in developing intrapreneurship among business students - Tambunan, Khairuddin Ependi; Hasibuan, Ali Fikri; Prayogo, Rangga Restu; Dongoran, Faisal Rahman; Syah, Dedy Husrizal; Sagala, Gaffar Hafiz (Journal of Education and Learning (EduLearn), 2024)
Intrapreneurship skill has considered as the alternative learning outcomes of entrepreneurship education. However, entrepreneurship teachers need a complex learning program to develop intrapreneurship among business students. At the same time, The Ministry of Education and Culture of The Republic of Indonesia recommends university teachers implement case methods to deliver complex learning environments and build critical skills among students.  Therefore, this study aims to i) examine the effect of micro small medium enterprise (MSME) cases on the intrapreneurship of business students, ii) investigate the influence of MSME cases on flow experience in entrepreneurship education and iii) investigate the effect of flow experience during entrepreneurship education on intrapreneurship skill.  We used field experiments on entrepreneurship and digital business student in business development courses.  The result indicates that the case method effectively developed student intrapreneurship skill and flow experience during the course positively impacting student intrapreneurship skill.